The duke and lady scandal - Carlyle, Christy (A Princes of London romance., 2025)
This opener of the Princes of London series takes readers on a breathless chase through Victorian London as a wild bluestocking from a family of treasure hunters and a handsome, serious gentleman from the Scotland Yard butt heads while attempting to thwart a plot to steal the Crown Jewels.